Uncovering Triradicaloid Structures in S1 Benzene Photochemistry** - Ayarde Henriquez, Leandro (Wiley, 2023)
Theoretical evidence concerning the multiradicaloid character in benzene photochemistry is reported based on a topological analysis of the correlated electron localization function. The bonding implications of triradicaloid conditions in both ground and excited states of S1 benzene are discussed within the bonding evolution theory. Our results suggest that triradicaloid/biradicaloid structures form due to the non-bonding density concentration over C atoms, causing the distorted geometry near the S1/S0 crossing. Biradicaloid centers formed in the excited state trigger new CC bonds, leading to a variety of photoproducts.
PUBLISHED